Base of professionality of teaching work in Rural Education - Wiama de Jesus Freitas Lopes; Emanuela Alves da Silva (Universidade Federal do Norte do Tocantins, 2018)
The article has as object of study the professional teaching base of the educators of the countryside and does it by the perspective of historical-dialectical materialism. Its objective is on the constitution of the teaching profession of educators of the field from their teaching functions in the Rural Education. His research question is: By what fundamentals and educational practices is the professional development of educators of the field developed in the multiseriate? This study has a bibliographic character and was developed in view of the dimensioning of the teaching work in the multiseries, concomitantly with the demands of human formation in the field. As part of the conclusive findings, this study reflects on the need for curricular (re) organization in light of the objective conditions of living and producing in the countryside, through social organization and the promotion of production systems. What, in rural schools, would refer to community planning for actions to demand or reorient public management models aimed at combating the social vulnerability of rural areas and overcoming situations of social exclusion, having as one of the contributions of this professionalism of the school educator and in the countryside.